Dysphagia in Pediatric Patients with Tracheostomy. (May 2022) - Luu, Kimberly; Belsky, Michael A.; Dharmarajan, Harish; Kaffenberger, Thomas; McCoy, Jennifer L.; Cangilla, Kristin; Tobey, Allison B. J.; Simons, Jeffrey P.; Maguire, Raymond; Padia, Reema
Objective: Post-tracheotomy swallowing function has not been well described in the pediatric population. This study aims to (1) determine differences in swallowing functioning pre- and post-tracheotomy and (2) examine the association between postoperative dysphagia and indication for tracheotomy, age at the time of tracheotomy, and time between tracheotomy and modified barium swallow (MBS). Methods: A retrospective chart review was performed on 752 patients who underwent a tracheotomy from 2003 to 2018 and had adequate documentation for review. Patients were included if they received a post-operative MBS. Descriptive statistics, logistic regression, and Fisher's exact test were used to analyze the data. Results: The cohort included 233 patients. The mean age at the time of tracheotomy was 25 months (±50.5). The indications for the tracheotomy were upper airway obstruction (110/233, 47.2%), chronic respiratory failure (104/233, 44.6%), and neurologic disease (19/233, 8.2%). The mean time from tracheotomy to post-operative MBS was 224 days (±297.7). Of the patients who had documented pre- and post-tracheotomy diets, nearly half of patients had improvement in their swallowing function after tracheotomy placement (82/195; 42.1%). Post-tracheotomy MBS recommended thickened liquids in 30.9% of the patients (72/233) and 42.5% (99/233) were recommended thin liquids. The remainder (62/233, 26.6%) remained nothing by mouth (NPO). Patients with neurological disease as the indication for the tracheotomy were more likely to remain NPO ( P = .039). Conclusion: A tracheotomy can functionally and anatomically affect swallowing in pediatric patients. The majority of our studied cohort was able to resume some form of an oral diet postoperatively based on MBS. This study highlights the need for objective measurements of swallowing in the postoperative tracheotomy patient to allow for safe and timely commencement of an oral diet. Level of Evidence: Level 3.